An Efficient Synthetic Approach to Substituted Trisphenols (Phloroglucide Analogues) Using Tungstosilicic Acid in Water - Fareghi-Alamdari, Reza; Khalafi-Nezhad, Ali; Zekri, Negar (Synthesis, 2014)
Tungstosilicic acid was found to be an efficient catalyst for the synthesis of trisphenols using the reaction of 2,6-bis(hydroxymethyl)phenols with phenols in an aqueous medium. The catalytic reactivity of tungstosilicic acid in boiling water was examined with a series of substrates, demonstrating that this catalyst is reactive in the presence of a variety of functionalities.
Keywords: tungstosilicic acid; trisphenols; phenols; 2,6-bis(hydroxymethyl)phenols; synthesis